Man-made mineral fiber size fractions and their interrelation. - Schneider, Thomas; Skotte, Jørgen; Nissen, Povl (Scandinavian Journal of Work, Environment & Health, 1985)
The fiber fractions RFOM (respirable fibers, determined by optical microscopy), SF (Stanton fibers), PF (Pott fibers), and FLOM (total length of optically visible, respirable fibers) and their ratios have been (i) determined experimentally in fiber sizes obtained by scanning electron microscopy of air samples of man-made mineral fibers and (ii) calculated theoretically for a range of fiber size distributions, assumed to be bivariate log-normal. For realistic values of fiber size parameters, RFOM and even FLOM are good predictors of Stanton and Pott fibers, the better the more-detailed the size information available is. The results point towards a possibility of estimating past exposure to Stanton or Pott fiber fractions of airborne man-made mineral fibers, even though only RFOM were determined.